(untitled) (Fiep Bulletin - online, 2016)
Adopting healthy habits is consensus as disease prevention strategy. In this context, regular physical exercise and its association with healthy food and the cronicidades control are effective health promotion methods. The rising costs of health services in conjunction with the rise of chronic noncommunicable diseases justifies the incentives for health care policies that stimulate change the organization of the current system to a preventive model. Seeking alignment with the current system needs, the National Health Agency (ANS) stimulates private health plans an offer services that seek to develop a comprehensive care of its beneficiaries. Thus, some carriers offer physical activities, nutrition programs and chronic management in the search for better health and quality of life for its customer base and thus reducing healthcare costs. The aim of the study was to analyze the impact of the practice of water aerobics participants in a health promotion program by the epidemiological profile analysis, anthropometric measurements and lifestyle. A cross-sectional survey was conducted with descriptive and analytical approach. The survey was conducted at the headquarters of a managed care plans in the city of Fortaleza, Ceará, in 2015. The survey sample was formed by 15 participants customers aerobics class for people over 50 years. Data were collected before individuals begin practicing aerobics and after three months of regular activity. Was observed with the study after three months of regular hydrogymnastics practice, 39% of participants reduced weight and BMI; 77% reduced fat percentage; 85% reduced waist circumference and 69% reduced blood pressure.